The Scientific Meaning of Fingerprints as Identity and Punishment in QS Al-Qiyamah (4) and Al-Anfal (12) - Ashila Uhnul Nafisa; Yeti Dahliana (Mauriduna : Journal of Islamic Studies, 2025)
The Qur'an mentions the term banaan (fingertips) in two different contexts, namely in QS Al-Qiyamah (4) and QS Al-Anfal (12), both of which contain scientific references that are relevant to modern knowledge. This study employed a qualitative method with a literature review approach to analyze the scientific meaning of banaan in both verses. The focus of the study was on the meaning of banaan as a symbol of human identity through fingerprints (QS Al-Qiyamah: 4) and as an object of punishment in the context of warfare (QS Al-Anfal: 12). Primary sources included Tafsir Al-Azhar, Tafsir al-Muyassar, and the works of Zaghlul al-Najjar, which were compared with modern anatomy, biology, and forensic literature. The results of the study indicated that QS Al-Qiyamah (4) affirms Allah's power in creating the unique identity of every human being through fingerprints, while QS Al-Anfal (12) describes the strategic dimension of attacks on vital points during the Battle of Badr. The novelty of this research lay in the integration of two meanings of identity and punishment in a single comparative analysis, which enhances the scientific approach studying of the Qur'an and opens up opportunities for the integration of modern science into Qur’anic exegesis (tafsir) studies.